Ethanol extracts of Rhynchosia nulubilis induce G2/M phase arrest by inducing deoxyribonucleic acid damage in human oral squamous cell carcinoma cells - Hwang, Young Sun (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Early cancer diagnosis is very important for cancer treatment and improvement of patient prognosis, but the development of effective cancer treatment agents is also necessary to overcome cancer. Accordingly, research is being actively conducted to derive ingredients that control cancer progression. Purpose: The antioxidant and anti-inflammatory effects of Rhynchosia nulubilis have been reported in various human cells. We attempted to ascertain the underlying mechanism by which the ethanol extracts of Rhynchosia nulubilis (EERN) induced cytotoxicity and cell cycle arrest in human oral squamous cell carcinoma (OSCC) cells. Methods: The EERN was prepared from the whole Rhynchosia nulubilis. A 3-(4,5 dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was performed for cytotoxicity of EERN in YD38 OSCC cells. A Matrigel-coated Transwell was used for invasion assay. Changes in the cell cycle distribution were monitored using fluorescence-activated cell sorting analysis. A phosphorylated form of H2AX (γH2AX) foci formation was observed using a fluorescence microscope. Results: Invasion activity of YD38 cells in a Matrigel-coated Transwell was significantly decreased by EERN in a dose-dependent manner. Cytotoxicity was observed at a treatment concentration of 8–10 mg/ml EERN, which induced Transwell invasion inhibition. The YD38 cells were more sensitive to EERN cytotoxicity than immortalized gingival fibroblasts. The EERN treatment arrested the YD38 cell cycle in the G2/M phase, and DNA damage marker γH2AX formation was increased by the EERN treatment. The phosphorylation of ataxia telangiectasia mutated and Chk2 was also increased by EERN treatment. Conclusion: These results indicate that EERN inhibits YD38 cancer cell growth and invasion activity through DNA damage and cell cycle arrest.